Retention and loss of immunoglobulin heavy chain alleles in helper T cell hybridoma clones. - Lonai, P (1983)
Retention or loss of immunoglobulin heavy chain genes was studied in 20 functional T cell hybridoma clones. DNA probes representing C mu, C alpha and JH genes, as well as VH subgroups II and III were hybridized with restriction enzyme fragments of hybridoma DNA by the Southern filter hybridization technique. Parental alleles of the hybridoma cells were distinguished on the basis of polymorphism of the lengths of restriction enzyme fragments. All clones retained the alleles of the lymphoma parent cell BW-5147 at all four loci. Thirteen clones lost both CH and VH alleles of the immune partner cell, whereas seven retained both VH alleles, and at least C alpha of the antigen-specific partner. Hence, T cell function in these cells is compatible with the loss of most immunoglobulin heavy chain alleles. This is interpreted to indicate either gene rearrangement and deletion, or chromosome loss. Accordingly, the T cell receptor is either controlled by two split gene loci in chromosome 12, at the two respective (5' and 3') ends of the mouse heavy chain gene family, or by a gene(s) outside chromosome 12.